The secret life of bees - Kidd, Sue Monk (Viking, 2002)
Set in South Carolina in 1964, [this book] tells the story of Lily Owens, whose life has been shaped around the blurred memory of the afternoon her mother was killed. When Lily's fierce-hearted "stand-in mother," Rosaleen, insults three of the town's fiercest racists, Lily decides they should both escape to Tiburon, South Carolina--a town that holds the secret to her mother's past. There they are taken in by an eccentric trio of black beekeeping sisters who introduce Lily to a mesmerizing world of bees, honey, and the Black Madonna who presides over their household. This is a remarkable story about divine female power and the transforming power of love--a story that women will share and pass on to their daughters for years to come.-Back cover.